Demographic and Clinical Characteristics of Chronic Low Back Pain Patients on Pregabalin: A Cross-Sectional Study at a Tertiary Care Hospital in Dhaka (Journal of Shaheed Suhrawardy Medical College, 2026)
Background: Chronic low back pain (CLBP) is a leading cause of global disability. While pregabalin is a common off-label treatment for CLBP, there is a significant gap in the literature regarding the demographic and clinical characteristics of the patient population receiving this medication, particularly in tertiary care settings in developing countries. This study aimed to describe the profile of these patients and observe changes in their pain over time.Methods: This was a cross-sectional study conducted at BIRDEM General Hospital in Dhaka from April to September 2024, involving 129 patients prescribed pregabalin for CLBP. Demographic, socio-economic, and clinical data were collected. The Visual Analog Scale (VAS) was used to measure self-reported pain intensity at baseline, and again at 6- and 12-week follow-up visits. The change in VAS scores was analyzed using a paired t-test by SPSS software (version 25.0) and then presented in tables and charts.Results: The study population had a mean (± SD) age of 52.3 ± 11.5 years and was predominantly female (61.2%). Common comorbidities included hypertension (38.0%), diabetes mellitus (29.5%), and ischemic heart disease (24.8%). The mean (± SD) duration of CLBP was 21.3 ± 9.8 months. Mean (± SD) VAS scores showed a progressive and statistically significant reduction from baseline (7.8 ± 1.1) to the 6-week (5.5 ± 1.4) and 12-week (4.2 ± 1.5) follow-up visits (p < 0.05).Conclusion: The findings characterize a complex and highly symptomatic patient cohort receiving pregabalin for CLBP. The significant reduction in pain intensity observed over a 12-week period is a promising real-world observation.J Shaheed Suhrawardy Med Coll 2024; 16(2): 87-91